The Effect of Muscle Flexibility on Passing Ability of Football - Ratiyono; Ramdan Pelana; Harry Syahputra Nasution; Ayu Purnama Wenly (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2022)
This study aims to determine the relationship between flexibility and passing skills in soccer games. This research is a type of correlational research. The population in this study were all players of Nuansa FC U 14-17 Padang City, totaling 25 players. This sampling was done by using a saturated sample technique, namely the entire population of the study, so the sample in this study was 25 football players Nuansa FC U 14-17 Padang City. The instrument used in this research is flexibility measured by sit and reach flexibility test and passing ability is measured using short pass test. The data analysis technique uses the product moment correlation analysis technique (simple correlation and multiple correlation) using SPSS with a significant level of = 0.05. The results of the study are that there is a significant relationship with r count of 0.863 between flexibility and passing skills in soccer players at SMA Negeri 15 Padang. . Based on the results of statistical analysis, it can be concluded that flexibility can affect the football passing skills of Nuansa FC U 14-17 players in Padang City.